The Development of High Order Thinking Skills (HOTS) Assessment Instrument for Temperature and Heat Learning - Aniq Rif’atun Najihah; Vina Serevina; Mutia Delina (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
Abstract The aim of this research is to develop the High Order Thinking Skills (HOTS) test instrument. The instrument was presented into a valid and reliable questionary to get information of the XI grade student's HOTS on temperature and heat. The research was done at Universitas Negeri Jakarta. The instrument has been trialed to 41 respondences on April 2018 at SMAN 1 Kabupaten Tangerang. The research was adapted from ADDIE approach which consists of Analyze, Design, Develop, Implement and Evaluate. The instrument consisted of 15 essays which the coefficient of reliability was 0.568, the difficulties and discrimination average were 0.817 and 0.363. Therefore the test instrument is proper to measure the student's HOTS.